2002
DOI: 10.1038/labinvest.3780418
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Envelope Glycoprotein 120 Increases Intercellular Adhesion Molecule-1 Expression by Human Endothelial Cells

Abstract: SUMMARY:Human immunodeficiency virus type 1 (HIV-1) infection is often associated with central nervous system damage and vascular complications. However, the mechanisms of this association are largely unknown. We examined the effect of HIV-1 envelope glycoprotein 120 (gp120) on cell adhesion molecule expression by endothelial cells. We found, for the first time, that both soluble and membrane-bound gp120 could significantly increase the expression of human endothelial intercellular adhesion molecule-1 (ICAM-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
43
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 51 publications
(57 reference statements)
5
43
0
1
Order By: Relevance
“…Gp120-induced expression of ICAM-1 was not caused by contaminating endotoxin in the gp120 preparation because polymyxin B did not inhibit the response. Moreover, antibodies against gp120 blocked gp120-induced responses in ICAM-1 expression (not shown), which is consistent with the results of Ren et al (2002) and our previous findings on gp120-induced monocyte migration (Stins et al, 2001). The gp120-mediated increases in ICAM-1 expression are mediated at the mRNA level, which is in accordance with the findings of Ren et al (2002).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Gp120-induced expression of ICAM-1 was not caused by contaminating endotoxin in the gp120 preparation because polymyxin B did not inhibit the response. Moreover, antibodies against gp120 blocked gp120-induced responses in ICAM-1 expression (not shown), which is consistent with the results of Ren et al (2002) and our previous findings on gp120-induced monocyte migration (Stins et al, 2001). The gp120-mediated increases in ICAM-1 expression are mediated at the mRNA level, which is in accordance with the findings of Ren et al (2002).…”
supporting
confidence: 81%
“…We were the first to show that gp120 can activate HBMEC from children in up-regulation of VCAM-1, intercellular adhesion molecule (ICAM)-1, and increased monocyte transmigration . Other investigators have also shown the gp120-mediated induction of ICAM-1 on endothelial cells derived from different origins: lung, skin, coronary artery, and umbilical vein (Ren et al, 2002). However, the underlying mechanisms involved in gp120-mediated activation of HBMEC are unclear (eg, roles of CD4, CCR3, CCR5, and CXCR4 receptors or other nonchemokine receptors).…”
mentioning
confidence: 99%
“…Endothelial dysfunction is present in ARV-naĂŻve HIV-infected patients, but improves only somewhat with introduction of ARV therapy, potentially due to negative effects of specific individual ARV drugs, virally-protein mediated endothelial activation (35), or chemokine dysregulation, with activation of macrophages, smooth muscle cells and enhanced atheroma formation. Data on direct infection of the vasculature are limited (36).…”
Section: Effects Of Hiv Infection On the Heart And Vasculaturementioning
confidence: 99%
“…Endothelial cells have been shown to be variably permissive for HIV infection. The HIV virus itself is able to penetrate coronary artery and brain microvascular endothelial cell membranes and to initiate inflammatory and biochemical intracellular reactions [198,199]. The activation of endothelium induced by either HIV infection itself or by a leukocyte-mediated inflammatory cascade triggered by the same virus leads to an increased expression of endothelial cellular adhesion molecules, such as intercellular adhesion molecule 1 (ICAM-1), vascular adhesion molecule 1 (VCAM-1], E-selectin, P-selectin, thrombomodulin, tissue plasminogen activator (tPA), and PAI-1.…”
Section: Clinical Sequelae Associated With Hiv and Hiv-lipodystrophymentioning
confidence: 99%